Challenges of Crisis Communication in Responding to the Threat of Terrorism: Minimizing Fear and Encouraging Community Solidarity - Sumadi, Sumadi; Nurteti, Lilis; Waluyo, Bambang Dwi; Niva, Matteson; Maharjan, Kailie (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Terrorism crisis has become one of the serious challenges in the context of global security. The threat of terrorism not only endangers the safety of individuals and communities but also causes widespread psychological impacts, such as fear and anxiety that can disrupt social harmony. In addressing the terrorism crisis, communication is the key to minimizing fear and fostering community solidarity. This study aims to explore effective crisis communication strategies in responding to terrorism threats. The main focus of the research is to understand how communication messages can be designed to reduce fear and rally support and solidarity among the community in the face of a terrorism crisis. The research method used is a qualitative study with a content analysis approach of various information sources such as policy documents, mass media, and interviews with crisis communication experts. These data are analyzed to identify effective communication strategies in a terrorism crisis situation. The findings show that communication strategies focused on delivering accurate, transparent information and providing clear guidance to the public can help reduce fear and build solidarity. Additionally, the use of narratives that emphasize values of togetherness and cooperation has also proven effective in garnering community support. The conclusion of this study is that effective crisis communication in responding to terrorism threats prioritizes clarity, accuracy of information, and the use of narratives that build solidarity. Well-planned and collaboratively executed communication strategies between the government, media, and community are key to facing communication challenges in the context of a terrorism crisis.